Endoscopy-assisted subfascial anterior transposition of the ulnar nerve for the treatment of cubital tunnel syndrome. Issue 12 (December 2016) - Wong, J.K.F.; Hsu, C.C.; Lin, C.H.; Lien, S.H.; Lin, Y.T.
Summary: Background: Many techniques have been described to relieve the compression and reduce subluxation of the ulnar nerve following surgery. The subfascial anterior transposition of the ulnar nerve (SfATUN) is one described technique, but involves a long scar, risk of injury to the medial antebrachial cutaneous nerve, and possible nerve ischemia from anterior transposition. We assessed a more refined approach of endoscopy-assisted SfATUN for the treatment of cubital tunnel syndrome. Methods: A consecutive case series of 21 patients (15 males and 6 females) with evidence of nerve subluxation after ulnar nerve decompression were operated using an endoscopy-assisted SfATUN. Each patient was assessed with pre- and postoperative nerve conduction studies, McGowan grading, and recovery of grip strength. Results: The average age of patients was 54 years (range 23–74 years), and they were followed up for a mean of 9 months (range 3–22 months). Preoperative McGowan grades were eight grade II and 13 grade III. Eighteen of the 21 patients showed improvement, including improvement by two McGowen grades in 8 patients and improvement by one grade in 10 patients. Three grade III patients did not show improvement in grading after surgery. A proportion of 90% of patients showed significant improvements in motor nerve conduction velocity of the ulnar nerve across the elbow ( p  < 0.001), and all showed some improvement in grip strength ( p  < 0.001). One patient underwent redo neurolysis. Conclusion: A combination of endoscopy-assisted SfATUN allows for decompression transposition and reduced strain on the ulnar nerve through a small scar. This is now our standard approach for cubital tunnel syndrome and the "unstable" nerve.